Audit Sistem Informasi Absensi Menggunakan Cobit 5 - Nurholis Nurholis; Joy Nashar Utama Jaya (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Dinas Penanggulangan Kebakaran dan Penyelamatan (DPKP) Penajam Paser Utara is a regional work unit that provides services in the field of fire and rescue. Currently DPKP implements an information system as an effort to improve employee work discipline. With a computerized tool using a fingerprint attendance machine that real records employee attendance. This system must be able to store, process, present and maintain information security properly. So it is necessary to conduct an audit to evaluate the system that has been running. In this study, the Cobit 5 Framework capability model is used as a EDM03, EDM05, APO06, APO12 dan DSS02suring tool for respondents' answers to questionnaires made according to the EDM, APO and DSS domain reference. The number of respondents involved in this study were 15 DPKP employees who routinely recorded attendance using an attendance machine. Based on the calculation of answers from respondents, the current capability level value is 3.05 in the range of 1-4. To get the expected results, several inputs and evaluations were made to improve employee discipline as well as a reference for improving the online attendance system at DPKP Penajam Paser Utara in the future.